Water quality index in the high-andean micro-basin of the Chumbao river, Andahuaylas, Apurímac, Perú - Choque Quispe, David (2021)
The water quality index (WQI) of a water body, indicates the degree of contamination for a given use, and it is related to the anthropic activities that they provoke around. The objective was to determine the WQI, in the high-Andean micro-basin of the Chumbao River, Andahuaylas, Peru. The section of study was included between the head of the basin (13°46'42.5" S, 73°13'50.0" W and 4 295 m of altitude), and last sampling point (13°35'26.4" S, 73°27'0.8" W and 2 529 m of altitude), with an average slope of 4%. The WQI Dinius was evaluated considering parameters such as oxygen level (DO and BOD5), eutrophication level (NO3 - and PO4 3-), physical characteristics (temperature, turbidity, color and TDS), dissolved substances (alkalinity, hardness, pH, conductivity and chlorides), and microbiological parameters (E. coli and total coliforms); it was sampled during the avenues season (02 lentic points and 08 lotics). The data were collected in triplicate, and analyzed through an ANOVA, Tukey test and Pearson's correlation at 5% significance. It was found that the predominant use of river water is for agriculture, pasture and urbanization; the WQI is divided into three categories Excellent (M1, M2, M3, M4 and M5) close to the head of the micro-basin and the lentic points (Pampahuasi and Paccoccocha lagoons), Acceptable (M6), and excessively contaminated points M7 and M8 outside the urban area downstream (p-value < 0.05); presenting a good negative correlation with the study parameters. In conclusion, the water in areas of low population density is good.